Critical Reflections on the Behavioural and Phenomenological Structures of Female University Students affecting Quality Education - Mir Alam Said; Alia (National University of Modern Languages (NUML), Islamabad, 2021)
The study critically examined the response of Pakistani female university learners and the perceptions of their teachers and department heads regarding the reflections on behavioural and phenomenological structures of female graduates in Pakistani universities affecting quality education. The main aim of the study is to analyze and find out the underlying considerations of the behavioural and phenomenological structures of female university students, and to assess the extent to which they affect the quality education at postgraduate level in Pakistan. This study has employed qualitative-survey design for identifying the factors deteriorating female university learners' attitude toward quality education, proficiency and caliber, and their collegial interactivity, evaluative performance and creativity. While using questionnaires, this survey enquiry investigated about the root causes of the problem and also about the gaps between psychologically sound behaviour and quality change. Responses were collected from 459 subjects i.e. 310 university learners, and their 111 teachers and 38 heads of university departments from 10 Pakistani leading universities located in Islamabad and Khyber Pakhtunkhwa Pakistan. By employing Chi-square, data were interpreted and statistically tested. The study found behavioural problem the female graduates faced in presenting quality performance affected by psychosocial phenomena. It also found the graduates' lacking competence required for quality education. It recommended for environment conducive for the self and learning, and also proposed the provision of facilitation for personality development for the Pakistani female postgraduate university learners.